Community and Circular Economy, Ancestral Andean Knowledge. Warmikuna NATABUELA Case - Almeida Guzmán, Marcia (2023)
The community entrepreneurship of Kichwa indigenous women, Warmikuna NATABUELA, reactivated its economy during the COVID-19 pandemic through agricultural activities carried out under the precepts of their culture and ancestral knowledge linked tothose of circular economy, where the value of the products and resources are maintained as long as possible, minimizing the generation of waste, contributing to a sustainable and efficient economy based on solidarity, reciprocity and redistribution. This research sought to make explicit, through an epistemological and methodological pluralism, that the andean indigenous peoples practiced the economic model today called circular as part of their worldview based on a deep respect for Pacha Mama. Through qualitative research, action-participatory research and community research, it was possible to recover oral memory through life stories of taytas, mamas and leaders of the town, which echoes an implicit community and circular economy in their empirical knowledge and in their own history. Concluding that the strengthening of their identity in synergy with scientific knowledge effectively contribute to economic development, environmental conservation and the social inclusion of the Andean peoples.